The impact of long-term care insurance on the subjective well-being of middle-aged and older individuals in rural China an empirical analysis based on CHARLS data - Liu, Zhenwei; Yang, Yinan; Mo, Guoli; Tan, Chunzhi; Zhang, Weiguo; Jia, Wei (Frontiers in Public Health, 2025)
The severe, often overlooked, mental health crisis among the aging population in rural China poses a pressing social challenge. This study investigates the role of a major policy intervention, Long-Term Care Insurance (LTCI), in enhancing their subjective well-being (SWB). Using panel data from the China Health and Retirement Longitudinal Study (CHARLS) for 2011–2020 and a multi-period difference-in-differences (DID) model, we find that LTCI implementation significantly improves the SWB of rural middle-aged and older residents. The underlying mechanisms include alleviated medical expenditure burdens, improved health status, and increased consumption. Crucially, our findings reveal a powerful equity-enhancing effect: the well-being benefits are substantially greater for the most vulnerable individuals—those with lower income, poorer health, and limited education. This study highlights LTCI’s vital function not only as a financial safety net but also as a crucial tool for promoting mental wellness and social equity in rural China. Policy should prioritize the expansion and optimization of LTCI to better support this at-risk demographic.